Designing task workflows to ensure the best scientific outcomes in citizen science - Sprinks, James C. (2017)
Citizen science, or ‘public participation in scientific research’, can be described as research conducted, in whole or in part, by amateur or nonprofessional participants often through crowd-sourcing techniques. The advance of modern day internet technology that has made the world a more connected place has resulted in a surge of citizen science projects, especially online platforms which allow volunteers to take part in research in both an asynchronous and geographically abstract manner. Due to this increased interest, citizen science is becoming a distinct field of research in its own right beyond the original scientific problems it was devised to address. Although some of this research has considered interface HCI and functionality, there has been relatively little attention paid specifically to human factors issues.